Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/jth.14750
|View full text |Cite
|
Sign up to set email alerts
|

Successful liver transplant from a hemophilia A donor with no development of hemophilia A in recipient

Abstract: Background Hemophilia A is an X‐linked inherited bleeding disorder caused by deficiency of coagulation factor VIII. Factor VIII is activated as part of the intrinsic coagulation cascade. It plays a crucial role as the cofactor in the intrinsic “tenase” complex activating factor X to assist in clot formation. Absence or mutation of this coagulation factor leads to excessive bleeding. Clinical manifestations of hemophilia relate to bleeding from impaired hemostasis, sequelae from bleeding, or complications of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Their studies showed that liver sinusoidal endothelial cells and extrahepatic cells (including the lung, spleen, kidney, brain, intestine, and tongue) did not express factor IX mRNA. In comparison, factor VIII is produced extrahepatically, and transplant of a liver from a donor carrying the diagnosis of hemophilia A did not lead to development of the bleeding disorder in the recipient [12][13][14][15].…”
Section: Discussionmentioning
confidence: 98%
“…Their studies showed that liver sinusoidal endothelial cells and extrahepatic cells (including the lung, spleen, kidney, brain, intestine, and tongue) did not express factor IX mRNA. In comparison, factor VIII is produced extrahepatically, and transplant of a liver from a donor carrying the diagnosis of hemophilia A did not lead to development of the bleeding disorder in the recipient [12][13][14][15].…”
Section: Discussionmentioning
confidence: 98%
“…However, the opposite is also true and several case reports describe the transmission of hemophilia through OLT, with phenotypes ranging from mild to severe in the recipient postoperatively (Table 3). [25][26][27][28][29][30][31][32] While numerous case reports indicate that hemophilia A donors can transmit the disorder to the transplant recipient, most recipients have mild disease due to extrahepatic synthesis of factor VIII in the recipient (Table 3).…”
Section: Hemophiliamentioning
confidence: 99%
“…No bleeding complications Normal factor VIII levels (likely due to extrahepatic production) Post-op elevated aPTT, PT attributed to heparin therapy, vitamin K deficiency Hemophilia A Kurian et al [26] No genotype testing found on the chart Hemophilia B Brunetta et al [28] Undiagnosed at the time of donation No diagnosis of bleeding disorder. In retrospect, had a history of large thigh hematomas after injury.…”
Section: Von Willebrand Diseasementioning
confidence: 99%
“…While FIX is clearly established as hepatocyte‐derived, FVIII mRNA has been found predominately in liver sinusoidal endothelial cells 48,49 . Some extrahepatic synthesis may occur as well 50 . Thus, targeting the liver with gene therapy directs transgene expression to hepatocytes, which for FVIII means expression in a heterologous cell type.…”
Section: The First Wave Of Haemophilia Gene Therapy From the 1980smentioning
confidence: 99%